The impact of age and neuroinflammation on the blood-brain barrier and neurovascular unit - Murray, Lorraine (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2012)
The barrier function of the blood-brain barrier (BBB) occurs primarily due to the presence of tight junctions (TJ) between endothelial cells of brain capillaries. Neurons, astrocytes, pericytes, basal lamina and extracellular matrix, collectively referred to as the "neurovascular unit" (NVU) are in close anatomical proximity to the endothelial cells and contribute to the establishment and maintenance of the BBB. With increasing age, there is a progressive decline in cognitive function (Anderton, 2002) and shift of the innate immune system towards a pro-inflammatory profile (Licastro et ai, 2005). It has been hypothesised that the BBB may become altered in the senescent brain (Ueno et ai, 2001; Farrall & Wardlaw, 2009) where an impaired BBB would facilitate the entry of neurotoxins into brain parenchyma and exacerbate any age-related tissue degeneration. Inflammatory cytokines, particularly IL-1β cause increased paracellular permeability in many peripheral tissues. Considering that the TJ proteins are essential in regulating BBB permeability, it is possible that the age-related increase in pro-inflammatory cytokines may disrupt TJ and contribute to BBB dysfunction with age. In this study, we report a functional disruption of the ageing BBB which facilitated the extravasation of exogenous sodium fluorescein and endogenous plasma albumin into the brain parenchyma, with a concomitant decrease in TJ protein expression. Structurally, the basal lamina of the NVU was fragmented and the expression of pericyte-specific proteins was reduced.
Keywords: Nursing & Midwifery, Ph.D.; Ph.D. Trinity College Dublin